2015
DOI: 10.1167/15.11.7
|View full text |Cite
|
Sign up to set email alerts
|

Role of early visual cortex in trans-saccadic memory of object features

Abstract: Early visual cortex (EVC) participates in visual feature memory and the updating of remembered locations across saccades, but its role in the trans-saccadic integration of object features is unknown. We hypothesized that if EVC is involved in updating object features relative to gaze, feature memory should be disrupted when saccades remap an object representation into a simultaneously perturbed EVC site. To test this, we applied transcranial magnetic stimulation (TMS) over functional magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…In addition, Irwin and Robinson (2015) found that the detection of stimulus displacement across saccades was capacity-limited and largely (but not exclusively) focused on the saccade target. It has also been demonstrated that a saccade disrupts VWM task performance when transcranial magnetic stimulation (TMS) is applied to parietal or early visual cortex presumably because TMS prevents the neurons maintaining the visual representation of the memory from undergoing remapping, thereby disrupting memory for that object (Prime et al, 2008;Malik, Dessing, & Crawford, 2015).…”
Section: Chapter 8: General Discussionmentioning
confidence: 99%
“…In addition, Irwin and Robinson (2015) found that the detection of stimulus displacement across saccades was capacity-limited and largely (but not exclusively) focused on the saccade target. It has also been demonstrated that a saccade disrupts VWM task performance when transcranial magnetic stimulation (TMS) is applied to parietal or early visual cortex presumably because TMS prevents the neurons maintaining the visual representation of the memory from undergoing remapping, thereby disrupting memory for that object (Prime et al, 2008;Malik, Dessing, & Crawford, 2015).…”
Section: Chapter 8: General Discussionmentioning
confidence: 99%
“…This ambiguity may therefore be a factor that led to modulation in both SMG and LOC. Dunkley et al (2016) accounted for the different responses in these regions (parietal RS vs. occipital RE) as the tendency of parietal cortex to respond better to Novel stimuli (Ardekani, Choi, Hossein-Zdeh, Porjesz, Tanabe, Lim et al, 2002; Linden, Prvulovic, Formisano, Voellinger, Zanella, Goebel, et al, 1999; Singh-Curry & Husain, 2009), versus occipital summation of pre- and post-saccadic feature information (Malik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the figure is summary of the cortical regions observed to be implicated within each spatial condition. Along with our results, we have also included areas that have been found to be involved in transsaccadic integration from previous studies (Prime et al, 2008; Prime et al, 2009; Tanaka et al, 2014; Malik et al, 2015). Lastly, we included links that represent possible underlying direct and indirect connections between the cortical regions we found here and the regions found in previous transsaccadic integration studies (Mishkin & Ungerleider, 1982; Sakata, Taira, Kusunoki, Murata & Tanaka, 1997; Culham & Kanwisher, 2001; James et al, 2002; Malach, Levy & Hasson, 2002; Grill-Spector et al, 2003; Goodale & Westwood, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations